Designing a Gardening Intervention to Improve Health: Recommendations From New and Experienced Gardeners. (7th June 2021) - Lukasik, Moriah; Bordner, Candace; Watt, Benjamin; Ho, Young; Veldheer, Susan
Abstract: Objectives: Gardeners consume more fruits and vegetables (F&V) and have lower body mass indexes (BMI) than non-gardeners, making gardening a potential public health intervention. Little is known about information needed to teach gardening skills to novice gardeners. This study investigated what never gardeners (NG) and experienced gardeners (EG) perceived as necessary information to teach gardening. Methods: Amazon Mechanical Turk (MTurk) workers responded to demographic and gardening questions via an online survey. After reviewing responses for completeness, 415 participants were included in the analysis. Participants were characterized by gardening experience level based on the total years they had gardened (0 years = NG, 1 + years = EG). In open ended questions, NG were asked: "What, if anything, would encourage you to start vegetable gardening?" and "What information do you think you would need to start a vegetable garden?" Experienced gardeners were asked "What information would be most important to teach someone who is new to vegetable gardening?" Qualitative responses were coded and the most frequent responses are presented. Results: The overall sample had a mean age of 40 years, was 47% female, 80% white, and 68% with a college degree. There were 203 NG (48.9%) and 241 EG (51.1%). For reasons that would motivate NG to start a garden, the two most frequently indicated were, 1 ) having the space needed to start a garden ( n  = 33, 16%) or 2 ) if it would be a way to save money (20, 9.7%). For NGs the most frequently mentioned response to what information they would need to start vegetable gardening on their own was information regarding maintenance, such as sunlight, water, weeding, and spacing ( n  = 30, 14.8%). For EGs the most frequent response to what information would be most important to teach someone new to vegetable gardening, was also information related to maintenance such as, such as sunlight, water, weeding, and spacing ( n  = 41, 17%). Conclusions: Gardening is a potential public health intervention that can influence health. Understanding space needs, costs of starting a garden, and knowing when to plant are key learning topics needed when developing these interventions for new gardeners. Future analyses will investigate the preferences and characteristics of those who would like to participate in an online versus an in-person gardening intervention. Funding Sources: None.